USING GAMES AS AN EFFICIENT WAY OF TEACHING VOCABULARY (American Journal of Research in Humanities and Social Sciences, 2023)
The following article defines significance of using games in teaching vocabulary for ESL learners. One of the most effective activities that support the students’ vocabulary are games. Games can help and encourage many learners to learn target language more easily.